Selección del reacondicionamiento de los pozos candidatos a procesos de optimización de producción en el campo Castilla mediante el análisis de las propiedades petrofísicas y el historial de producción del campo (2020)
This investigation aims to make the selection of the work over of the candidates Wells for production optimization process in the Castilla Field through the analysis of the petrophysical properties and the production history of the field. To achieve this purpose the Heterogeneity index graph was made, which is an “cross-hair plot” of a sample of 199 wells in the southern sector of the Castilla Field of the production units K1, K1-Lower and K2, in wich it was made a preliminary selection of 109 wells which are below of the production average of the field. To these Wells, a thorough analysis of their Heterogeneity Index plots, productivity index plot, flow capacity, flow rate, and mechanical state of each well was carried out to determine which work over will be recommended. Four (4) families of wells were found; they were hydraulic fracturing (10 wells), isolation of zones (20 wells), isolation of zones with new perforations (20 wells) and new zones perforation (5 wells), apart it was observed that five (5) of the selected Wells required a well service at is the change or redesign of the pump.